Metformin and Colorectal Cancer - Higurashi, Takuma; Nakajima, Atsushi (Frontiers in Endocrinology, 2018)
Colorectal Cancer (CRC) is one of the most commonly encountered neoplasms worldwide. The incidence of CRC has been increasing and new strategies for prevention, including chemoprevention, are needed to lower the burden of this disease. Metformin is a biguanide derivative that is widely used for treating diabetes mellitus. Many recent reports, include basic research, epidemiological, and clinical trial studies, indicated that metformin has benefits not only in diabetes treatment, but also in lowing the risk of developing cancer (including CRC). This evidence suggests that metformin may be a candidate agent for CRC chemoprevention. This review article shall discuss the present evidence of metformin treatment and CRC, and outline our challenge in basic research and clinical studies of metformin as chemoprevention for colorectal tumors.